Variations, sources, and effects on ozone formation of VOCs during ozone episodes in 13 cities in China - Shan, Danying; Du, Zhenyu; Zhang, Ting; Zhang, Xiulan; Cao, Guan; Liu, Zirui; Yao, Zhixiao; Tang, Ka; Liang, Siyuan (Frontiers in Environmental Science, 2023)
In recent years, ozone (O3) pollution has worsened in China and contributes frequently to air pollution problems due to the continuous increasing emission of volatile organic compounds (VOCs). To support the implementation of coordinated control for ozone and fine particulate matter, it is essential to study the chemical compositions and sources of VOCs, which are the crucial precursor of both ozone and fine particulate matter. In this study, 117 volatile organic compounds were monitored in 13 cities in Beijing-Tianjin-Hebei Urban Agglomeration and Fenwei plain. Concentrations of total VOCs ranged from 42 µg/m3 to 279 µg/m3 during the monitoring episode. In all 13 cities, alkanes, halogenated hydrocarbons, aromatics and oxygenated volatile organic compounds (OVOCs) were the dominant VOCs. Contributions of alkanes, halogenated hydrocarbons, aromatics and OVOCs to total ozone formation potential (OFP) were 21.7%-32.6%, 21.0%-27.9%, 24.3%-50.8% and 28.6%-52.3%, respectively. Further, the results of source apportionment by positive matrix factorization (PMF) model indicated that solvent usage, gasoline evaporation, vehicle emissions, petrochemical industry and combustion were essential VOCs sources in 13 cities. Moreover, the sensitivity of ozone production was studied using an empirical kinetic modeling approach (EKMA) model, and it was found that ozone formation was VOCs-limited in all 13 cities.